5W+1H QUESTIONS IN ENHANCING STUDENTS’ WRITING ABILITY - ST MARHANA RULLU (JURNAL PENDIDIKAN GLASSER, 2019)
Writing is language ability that very important for all human life. Writing helps someone to think easily and to express all idea, thought and feeling existing in mind in written form. The purpose of this research is to explore 5W+1H Questions in enhancing students’ writing ability at Eleventh grade in Madrasah Aliyah Negeri 2 Banggai. This research used Classroom Action Research (CAR). It consists of two cycles (cycle 1 and cycle 2). This research was conducted in 4 stages, namely: planning, action, observation and reflection. The result of this research had enhanced the students’ writing ability through 5W+1H Questions, it can be seen by the mean score of students in each cycle. The percentage of completeness in pre-cycle was 61,4% and first cycle of meeting at 72,3% while the post-test was 90,3%. It indicated 5W+1H Questions enhanced the students’ writing ability.